Surgical Outcome in Bentall’s Procedure - Rajbanshi, Bijoy; Timala, Rabindra; Pradhan, Sidhartha; Singh, Yogesh Man; Gautam, Navin; Sharma, Jotindra; Koirala, Ramesh; Koirala, Bhagwan (Nepalese Heart Journal, 2008)
It is well recognized that Bentall's procedure is one of the demanding surgeries in adults. We report the short term results following Bentall’s procedure in seventeen consecutive patients operated in the last 5 years.